ANALISIS METODE SYARAH HADIS SYAIKH MUHAMMAD AL-AMIN AL-HARARI DALAM AL-KAUKAB AL-WAHHAJ SYARAH SAHIH MUSLIM - Hifdhul Ulum; Mohammad Anang Firdaus (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
Shaykh Muhammad al-Amin al-Harari is one of the scholars who is known to master many fields of religious science, especially tafsir, hadith, language, fiqh, but many academics have studied him in terms of his interpretation and there is still no research that discusses him in terms of hadith. Therefore, the researcher reviews the biography and contribution of Shaykh Muhammad Amin al-Harari in the field of Hadith by looking at how the method of Hadith narration he used in the book of Sahih Muslim that he wrote and what composition he used in narrating the Hadith of Sahih Muslim. Through the library research method, therefore this research needs data sources in the form of the book of al-Kaukab al-Wahhaj, the book of the method of hadith scribing and scientific journals related to this discussion. To get perfect results, the analysis of this research is carried out by discussing the book of hadith analysis methods and scientific journals and comparing the book of hadith analysis of sheikh Muhammad Amin al-Harari with the book al-Minhaj. this research concludes that the method of sheikh Muhammad Amin al-Harari in synthesizing the hadith of the Sahih Muslim book is the tahlili and muqarin method. the composition Syarah hadis used by sheikh Amin al-Harari includes: explanation of the narrator of the hadith, fiqh, description of the lafadz, nahwu, differences of opinion of scholars (ikhtilaf) in understanding the hadith, differences in the lafadz of hadith narration.